Approaches to triage optimization in HPV primary screening: Extended genotyping and p16/Ki‐67 dual‐stained cytology—Retrospective insights from ATHENA. Issue 9 (6th October 2019) - Stoler, Mark H.; Baker, Ed; Boyle, Sean; Aslam, Shagufta; Ridder, Ruediger; Huh, Warner K.; Wright, Thomas C.
Abstract : The objective of our study was to assess the performance of different triage strategies for high‐risk human papillomavirus (hrHPV)‐positive results utilizing either extended genotyping or a p16/Ki‐67 dual‐stained cytology (DS) approach, with or without partial genotyping. A subset of women with hrHPV infections participating in the Addressing the Need for Advanced HPV Diagnostics (ATHENA) study were analyzed to determine the number of cervical intraepithelial neoplasia grade 3 or worse (≥CIN3) cases detected, and the absolute risk for ≥CIN3 of each genotype. A clinical utility table was constructed to compare the impact of different triage strategies. In all, 2, 339 women with single‐genotype hrHPV infections were identified. Among these were 171 ≥CIN3 cases. The U.S. Food and Drug Administration (FDA)‐approved algorithm (HPV16/18 positive, or 12‐other hrHPV positive and Pap positive, i.e., ≥ atypical squamous cells of undetermined significance) for primary HPV screening detected 132/171 (77.2%) ≥CIN3 cases and required 964 colposcopies (colposcopies per ≥CIN3 ratio: 7.3). An approach that uses DS instead of cytology in the FDA‐approved algorithm detected 147/171 (86.0%) ≥CIN3 cases, requiring 1, 012 colposcopies (ratio: 6.9). Utilizing DS for triage of all hrHPV‐positive women identified 126/171 (73.7%) ≥CIN3 cases, requiring 640 colposcopies (ratio: 5.1). A strategy that detected HPV16/18/31/33/35+ captured 130/171 (76.0%) ≥CIN3 cases, requiring 1, 025 colposcopies (ratio: 7.9). Inclusion of additional genotypes resulted in greater disease detection at the expense of higher colposcopy ratios. Substituting cytology with a DS triage approach improved disease detection and the colposcopy detection rate. Further reduction of colposcopy rates can be achieved by using DS without partial genotyping. Extended genotyping strategies can identify a comparable number of cases but requires an increased number of colposcopies. Abstract : What's new? Among HPV‐positive women, the goal is to maximize the number of CIN3 or greater cases detected while minimizing colposcopies. These authors compared various combinations of genotyping and dual‐stained cytology (DS) as triage strategies. From a pool of 2, 339 hrHPV+ women, 171 cases with ≥CIN3 were identified. Only one algorithm they tested boosted sensitivity over the current approach without reducing specificity. This method used DS to triage women who tested positive for 12‐other HPV, and referring HPV16/18+ patients directly to colposcopy. This approach caught 147 of the 171 cases, while reducing the number of colposcopies per case from 7.4 to 6.9.